THE ROLE OF FINANCIAL KNOWLEDGE ON LIFE INSURANCE AND FAMILY TAKAFUL AWARENESS - Lim Thien Sang; Mohidin, Rosle; Ag Budin, Dg Safrina (Malaysian Journal of Business and Economics (MJBE), 2020)
The Government of Malaysia wants national life insurance and family takaful penetration rate to breach 75 per cent by the end of 2020. It realises that to attain this goal, it has to raise the population’s awareness of the benefits of life insurance and family takaful. Central Bank’s data from 2017 revealed the life insurance penetration rate and ownership in Malaysia were discouraging. The penetration rate was reported at 56 per cent, meaning there is another 19 percentage point to cover to reach the 2020’s target. Ownership level was also low as only about one-third of the populations and less than 20 per cent of adults were protected by life insurance. One explanation that links the low level for life insurance demand among Malaysians is their inability to objectively evaluate the benefits of life insurance protection. It has been suggested in the literature that a lack of financial knowledge would hinder one’s ability to interpret financial information accurately. Thus, it is fair to believe that the level of financial knowledge will have a direct effect on life insurance and facility takaful awareness, and eventually the demand for life insurance products. The main purpose of the paper discusses the literature linking financial knowledge and life insurance awareness. Some suggestions on how to alleviate life insurance awareness among Malaysians are also included.